How Family Environment Influences Teens - Donna Davis (EDIS)
“After years of hearing how much I should dread the teen years, what a wonderful surprise it was when I found that living with teenagers could actually be not just a pleasant experience, but a fulfilling and wonderful adventure…” This transcript of a two-minute Family Album Radio broadcast was published by the UF Department of Family, Youth and Community Sciences, March 2012.